The generalized De Rham-Hodge theory of Delsarte transmutation operators in multidimension case and its applications - Prykarpatsky, Y.A.; Samoilenko, A.M. (Нелінійні коливання, 2004)
A study of spectral and differential-geometric properties of Delsarte transmutation operators is given. Their differential geometrical and topological structure in multidimension is analyzed, the relationships with the generalized De Rham – Hodge theory of generalized differential complexes are stated. Some applications to integrable dynamical systems in multidimension are presented.